COMPLEX EVALUATION OF HIGH TECHNOLOGICAL MEDICAL CARE FOR CARDIOLOGIC PATIENTS AND RESPECT FOR THESE CARE PRODUCTS IN THE POPULATION OF THE SAMARKAND REGION (LITERARY REVIEW) - Rizaev Jasur Alimzhanovich; Saidov Maksud Arifovich; Farida Odylovna Khasanjanova (Scholar Express Journals, 2023)
This article reviewed the incidence of cardiovascular diseases (CVDs) and the causes of morbidity, mortality and disability from these diseases worldwide, including in Uzbekistan. The prevalence of high-tech medical care (HMC) and the role of HMC in reducing complications, mortality and disability due to (CVD) was studied.
Keywords: high-tech medical care; cardiovascular diseases; mortality; morbidity